2012
DOI: 10.1016/j.jtbi.2011.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial network structure and metapopulation persistence

Abstract: We explore the relationship between network structure and dynamics by relating the topology of spatial networks with its underlying metapopulation abundance. Metapopulation abundance is largely affected by the architecture of the spatial network, although this effect depends on demographic parameters here represented by the extinction-to-colonization ratio (e/c). Thus, for moderate to large e/c-values, regional abundance grows with the heterogeneity of the network, with uniform or random networks having the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 21 publications
7
96
1
Order By: Relevance
“…The landscape structure of our IBM was modelled as four different types of networks (figure 1) of increasing heterogeneity: regular, random, exponential and scale-free [35] (note that landscape and network are used interchangeably). To understand the effects of network heterogeneity, all networks were set with the same number of nodes (n p ¼ 1024 patches), edges (n c ¼ 4096 connections) and average degree (eight connections per patch).…”
Section: Materials and Methods (A) Landscape Structurementioning
confidence: 99%
“…The landscape structure of our IBM was modelled as four different types of networks (figure 1) of increasing heterogeneity: regular, random, exponential and scale-free [35] (note that landscape and network are used interchangeably). To understand the effects of network heterogeneity, all networks were set with the same number of nodes (n p ¼ 1024 patches), edges (n c ¼ 4096 connections) and average degree (eight connections per patch).…”
Section: Materials and Methods (A) Landscape Structurementioning
confidence: 99%
“…Thus a patch will benefit more if it is connected to a higher degree patch, and the effect may be larger than the patch's own degree. Therefore, if we target to inactivate the hubs, the metapopulation persistence decreases [17]. In all the cases, the abundance of the metapopulation is very high until the inactivation ratio p reaches a critical value p c , but in the case of random inactivation the chances of metapopulation persistence are higher compared to targeted inactivations.…”
Section: Complex Dispersal Networkmentioning
confidence: 99%
“…Like physicists, ecologists are also placing more importance on the study of networks of coupled oscillators. The rationale behind studying complex networks lies in the fact that the network topology highly affects its dynamics and some recent papers have explicitly investigated the dynamical consequences of network patterns [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, it will be important to independently assess the realism of these different extinction scenarios, as each of these scenarios result in different subsequent extinctions (Srinivasan et al 2007). Moreover, the network models used here were conservative in that they only took into account the topological structure of the herbivore-plant network, and these types of analysis may underestimate extinction risks, as they fail to account for interaction strengths between species and the resulting changes to population dynamics (Gilarranz and Bascompte 2012). Moreover, in a previous study, we showed that there is a relationship between the specificity of host plants by the larval and adult stages of these Lepidopterans, but that the strongest specificity is in the larval stage (Altermatt and Pearse 2011).…”
Section: Modeling Extinction Cascades Using Realistic Extinction Scenmentioning
confidence: 99%